Report to the Congress by the U.S. Maritime Commission of Action Taken under Section 217 of the Merchant Marine Act, 1936, as Amended (P.L. 498, 77th Cong.), on Freight Forwarding. (U.S. Congressional Research., 1948)
Jan. 30, 1948 to June 7, 1948; includes list of freight forwarders cleared by U.S. Maritime Commission as eligible to participate in the forwarding of U.S. government export shipments.